Pangasinan’s Best: Microplastics Properties Found in Pangasinan Mangrove crab (Scylla serrata) Production - De Castro, Jediaelle Denise Y. (Animo Repository, 2023)
Microplastic consumption is a pressing global issue, yet it has received limited attention in the Philippines. This lack of awareness may lead to health problems among Filipinos, as microplastics can contain harmful substances that disrupt human processes and cause diseases. To address this, a study was conducted in Dagupan City, Pangasinan, focusing on microplastic properties in Scylla serrata production. Samples were collected and examined under a light compound microscope, while in-person observations and interviews with mangrove crab growers provided data on the crabs' environment. Of the 120 samples, 30 mangrove crabs were analyzed, with each crab having four subsamples. Results revealed that 33.33% of the observed crabs had intense contamination, 30% had prevalent contamination, 13.33% had medium contamination, and 16.67% were slightly contaminated. Only 6.67% of the crabs were free from microplastic contamination. Fiber was the most dominant type of microplastic, accounting for 33.33% of the overall contamination. These findings indicate a significant presence of microplastics in the collected mangrove crabs, suggesting that many crabs consumed by humans are contaminated. The Philippine government has responded to this ecological problem by enacting the Extended Producers Responsibility Law (EPR Law), which mandates large companies to implement comprehensive and eco-friendly solid waste management programs.